Can anyone help with these proofs? Prove the following formulas for changing from one base to another: a) log_b x = (log_b a)(log_a x) b) log_b x = (log_a x)/(log_a b) Thank so much
Follow Math Help Forum on Facebook and Google+
Originally Posted by Percent09 Can anyone help with these proofs? Prove the following formulas for changing from one base to another: a) log_b x = (log_b a)(log_a x) b) log_b x = (log_a x)/(log_a b) Thank so much Log_a x = P log_b x = Q log_b a = R A^P = b^Q = x (b^R)^P = b^Q b^RP = b^Q RP = Q P = Q/R log_a x = (log_b x / log_b a) Just modify it to suit your question.
I cant seem to find (a) in my maths book... Could you just double check your post?
View Tag Cloud